2017
DOI: 10.21577/0103-5053.20170124
|View full text |Cite
|
Sign up to set email alerts
|

Potential Bio-Oil Production from Invasive Aquatic Plants by Microscale Pyrolysis Studies

Abstract: The invasive aquatic plants Eichhornia crassipes (water hyacinth), Eichhornia azurea, and Nymphaea spp. were evaluated as sources of lignocellulosic biomass for the production of bio-oil. These plants have high growth rates that can lead to various environmental problems and the production of large amounts of waste biomass. The materials were characterized in terms of their contents of moisture, oil, and ash, and by analysis using thermogravimetry, infrared spectroscopy (IR), elemental analysis, and energy dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In the samples of aquatic macrophytes we studied, we did not find heptanoic and gallic acids. However, there is ample evidence regarding the presence of heptanoic acid in the composition of metabolites of aquatic macrophytes [41]. In addition, there are results that heptanoic and octanoic acids, being allelochemicals of aquatic macrophytes, can lead to suppressing the development of cyanobacteria [42].…”
Section: Discussionmentioning
confidence: 99%
“…In the samples of aquatic macrophytes we studied, we did not find heptanoic and gallic acids. However, there is ample evidence regarding the presence of heptanoic acid in the composition of metabolites of aquatic macrophytes [41]. In addition, there are results that heptanoic and octanoic acids, being allelochemicals of aquatic macrophytes, can lead to suppressing the development of cyanobacteria [42].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Gulab et al [32] was reported that pyrolysis of water hyacinth using Cu and Al catalyst produce BCO with aliphatic hydrocarbons and aromatic hydrocarbons. Santos et al [31] reported BCO produced by pyrolysis of water hyacinth with the composition of o-benzenediol, glycerol, p-benzenediol, hexadecanoic acid, arabinoic acid, and levoglucosan and composed of phenols, furans, and nitrides were interpreted by Huang et al [37]. Pyrolysis experiments with the second raw materials (a mixture of cassava solid waste and palm oil) produced the GC chromatograms presented in Figure 4.…”
Section: Gc-ms Analysis Of Pyrolysis Productsmentioning
confidence: 98%
“…The types of components are also very similar. Several workers have conducted pyrolysis of cassava solid waste, however, the main purpose of the studies was for the production of biochar [29][30][31][32]. For the production of BCO, pyrolysis of cassava solid waste was described by several workers with various compositions.…”
Section: Gc-ms Analysis Of Pyrolysis Productsmentioning
confidence: 99%
“…The roots of the water hyacinth plants were removed and discarded, and the plants were washed in running water and left to dry for three days in the open. Then, the stems and leaves were separated and placed in an oven at 50 • C for 24 h [20]. After the drying process, they were ground separately and left in an oven at 45 • C for 24 h, and finally, sieved using a 425 µm particle size sieve.…”
Section: Preparation Of Adsorbent Materialsmentioning
confidence: 99%